MOA-2010-BLG-311: A planetary candidate below the threshold of reliable detection - Yee, J.; Hung, L.; Bond, I.; Allen, W.; Monard, L.; Albrow, M.; Fouque, P.; Dominik, M.; Tsapras, Y.; Udalski, A.; Gould, A.; Zellem, R.; et al. (Institute of Physics Publishing, 2013)
We analyze MOA-2010-BLG-311, a high magnification (Amax > 600) microlensing event with complete data coverage over the peak, making it very sensitive to planetary signals. We fit this event with both a point lens and a two-body lens model and find that the two-body lens model is a better fit but with only ??2 ~ 80. The preferred mass ratio between the lens star and its companion is q = 10-3.7±0.1, placing the candidate companion in the planetary regime. Despite the formal significance of the planet, we show that because of systematics in the data the evidence for a planetary companion to the lens is too tenuous to claim a secure detection. When combined with analyses of other high-magnification events, this event helps empirically define the threshold for reliable planet detection in high-magnification events, which remains an open question.